PEAK DISCHARGE ESTIMATION OF WELANG WATERSHED IN PASURUAN REGENCY: Estimasi Debit Puncak DAS Welang Di Kabupaten Pasuruan - Febriyanto, Andreyan; Hidayah, Entin; Halik, Gusfan (Jurnal Rekayasa Sipil dan Lingkungan, 2018)
Peak runoff has an important role in flood control.In flood control, the data of peak runoff is needed to anticipate the flood and rain fall modeling estimation is required with the help of HEC-HMS Software. From modeling result on February 3, 2007 researcher got calibration value of simulation of peak discharge 17,9 and peak discharge observation is 16,7 with a value of effectiveness (Nash) of 0.873. Model validation test on 9,10 February and 7 March 2007 resulted in value (Nash) of 0.826, 0.742 and 0.656. Debit puncak mempunyai peranan penting dalam pengendalian banjir. Dalam pengendalian banjir, data dari limpasan hujan dibutuhkan untuk mengantisipasi banjir dan pemodelan estimasi curah hujan dibutuhkan dengan adanya bantuan dari Software HEC-HMS. Hasil pemodelan pada tanggal 3 Februari 2007 didapat nilai kalibrasi simulasi debit puncak sebesar 17,9 mÂ³/s dan observasi debit puncak sebesar 16,7 mÂ³/s dengan nilai efektifitas (Nash) sebesar 0,873. Uji validasi model pada tanggal 9,10 Februari dan 7 Maret 2007 menghasilkan nilai (Nash) sebesar 0,826, 0,742 dan 0,656.